INTIMA-MEDIA THICKNESS AND ADHESION MOLECULES SICAM-1 AND SVCAM-1 IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: CLINICAL AND DIAGNOSTIC VALUE - S. G. Kasatkina; T. N. Panova (Российский кардиологический журнал)
Aim. To study the associations between the intima-media thickness (IMT) of common carotid artery and the expression of soluble adhesion molecules sICAM‑1 and sVCAM‑1 in patients with Type 2 diabetes mellitus (DM‑2). Material and methods. The study included 97 DM‑2 patients (50 men and 47 women), aged 45–70 years (mean age 52,25±5,62 years). All participants underwent in-hospital standard clinical examination, risk factor assessment, electrocardiography, and duplex ultrasound of extracranial vessels (“Vivid 3” TM device, USA; linear transducer 7,5 MHz), as well as the measurement of blood levels of soluble adhesion molecules sICAM‑1 and sVCAM‑1. Results. There was a statistically significant correlation between common carotid artery IMT and the levels of sICAM‑1 and sVCAM‑1 (р<0,05). Conclusion. The results obtained suggestthatthe levels of adhesion molecules sICAM‑1 and sVCAM‑1 could be a marker of atherosclerotic progression in DM‑2 patients.